Effectiveness and safety of herbal medicine Ukgansan for clinical symptoms in Parkinson's disease: A pilot, randomized, assessor-blinded clinical trial - Jin, Chul; Cho, Ki-Ho; Kwon, Seungwon; Lee, Han-Gyul; Kim, Tae-Hun; Jung, Woo-Sang; Moon, Sang-Kwan; Cho, Seung-Yeon; Kang, Byoung-Kab; Park, Jung-Mi; Park, Hi-Joon; Ko, Chang-Nam (Frontiers in Neurology, 2022)
Objectives: Parkinson's disease (PD) is a neurodegenerative disease in which patients are suffering various symptoms. Previous experimental studies suggested that herbal medicine Ukgansan (UGS) could be beneficial for PD. The aim of this pilot clinical trial was to evaluate the efficacy of UGS for improving clinical symptoms in patients with PD. Methods: Sixty patients with idiopathic PD were randomly assigned to receive either UGS plus acupuncture or acupuncture alone for 6 weeks. During the trial, all anti-parkinsonian medications were maintained. Subjects were evaluated for various clinical assessments of PD, including the Movement Disorder Society-Sponsored Revision of the Unified PD Rating Scale (MDS-UPDRS) and the 39-item Parkinson's disease questionnaire (PDQ-39), until 12 weeks. Results: In MDS-UPDRS between the groups, no significant time x group interaction was found. In subgroup analysis of anxiety participants, significant time x group interaction was found in the PDQ-39 domain of mobility (P=0.007), activities of daily living (P=0.042), and the PDQ-39 summary index (P=0.048). In addition, post-hoc analysis in anxiety participants showed a significant decrease in the domains of mobility (P=0.001) and activities of daily living (P=0.013) at weeks 7. There were no adverse events associated with UGS. Conclusions: The additional administration of UGS has the potential to significantly improve the quality of life of PD patients with anxiety. In order to create more definitive evidence, clinical trials with more rigorous methodologies should be conducted in the future. This trial is registered with Korean Clinical Trial Registry (http://cris.nih.go.kr; registration number: KCT0003444).